Multilateralism versus Regionalism!? - Marco Wagner; Bernhard Herz (Verein für Socialpolitik, 2010)
The well-known question whether regional trade agreements (RTAs) and the multilateral trading system (MTS) are strangers, friends, or foes (Bhagwati and Panagariya, 1996) has gained new importance with the widespread proliferation of RTAs in recent years. Based on an extensive data set which covers most of world trade over the past 60 years and about 240 regional trade agreements, we analyze the relationship between RTAs and the MTS by combining the gravity model framework with vector auto-regression analysis. Impulse-response-functions robustly suggest that multilateral trade liberalization responds in a significantly positive way to regional trade liberalization. We also find robust evidence that RTA liberalization Granger-causes GATT/WTO liberalization. Thus, our results indicate that RTAs do not undermine the MTS but serve as building blocs to multilateral trade liberalization.
Keywords: F13; F15; F10; 330; Regionalism; multilateralism; trade agreement; gravity model